2004
DOI: 10.1111/j.1365-2958.2004.04225.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of SOS expression in individual Escherichia coli K‐12 cells using fluorescence microscopy

Abstract: SummaryMany recombination, DNA repair and DNA replication mutants have high basal levels of SOS expression as determined by a sulAp-lacZ reporter gene system on a population of cells. Two opposing models to explain how the SOS expression is distributed in these cells are: (i) the 'Uniform Expression Model (UEM)' where expression is evenly distributed in all cells or (ii) the 'Two Population Model (TPM)' where some cells are highly induced while others are not at all. To distinguish between these two models, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
185
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(198 citation statements)
references
References 59 publications
12
185
1
Order By: Relevance
“…In one positive control, lexA(Def) (SOS repressor-null) cultures fluoresce green quantitatively (Fig. 1a) 6 , and two negative controls, SOS-uninducible lexA(Ind − ) or ΔrecA cells, show 2 × 10 −4 ± 0.1 × 10 −4 and 7 × 10 −4 ± 4 × 10 −4 green cells (mean ± s.e.m. ), respectively ( Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In one positive control, lexA(Def) (SOS repressor-null) cultures fluoresce green quantitatively (Fig. 1a) 6 , and two negative controls, SOS-uninducible lexA(Ind − ) or ΔrecA cells, show 2 × 10 −4 ± 0.1 × 10 −4 and 7 × 10 −4 ± 4 × 10 −4 green cells (mean ± s.e.m. ), respectively ( Fig.…”
mentioning
confidence: 99%
“…RecA bound to ssDNA promotes proteolysis of the LexA transcriptional repressor, increasing expression of more than 40 SOS damage response genes4. We engineered wild-type E. coli to carry a chromosomally located gfp gene encoding green fluorescent protein (GFP) controlled by the SOS-inducible sulA promoter 6 , which causes cells with SOS-inducing DNA damage to fluoresce green (that is, these cells are GFP + ). Because it is not plasmid borne and does not inactivate any gene (including sulA), damage is detected without perturbing levels of proteins that affect DNA damage processing (Supplementary Methods online).…”
mentioning
confidence: 99%
“…The SS996 has a mutation in ftsZ that makes the protein insensitive to the SOS-induced cell division inhibitor SulA, thus allowing continued growth of the cells in conditions that would otherwise induce the SOS response and inhibit cell growth [22,23]. It has been reported that β-lactams and fluoroquinolones induce SOS response that temporarily inhibit cell division and help bacteria survive their lethal effects [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this striking difference of regulation are unknown but could be the result of a difference in the fraction of the cell population spontaneously expressing the SOS response between V. cholerae and E. coli (57). Indeed, exposure to DNA-damaging agents that are known to induce the SOS response (UV light, mitomycin C, ciprofloxacin) have been shown to stimulate SXT conjugative transfer at frequencies up to 10 -2 per donor (58).…”
Section: Regulation Of Excision and Conjugative Transfermentioning
confidence: 99%